A proposed model for sustainable business excellence. Issue 2 (19th November 2019) - Jabnoun, Naceur
Abstract : Purpose: The purpose of this paper is to develop an excellence model that combines noble ends and noble means to achieve sustainable business excellence (SBE). Design/methodology/approach: The general framework of existing excellence models is used to develop the new model. Relevant literature on business excellence and current business and economic trends such as constructive capitalism, conscious capitalism, shared value, values-driven organizations and corporate governance are used to develop the basic concepts of the model. The criteria and the assessment method of the model are then developed based on the basic concepts. Findings: This paper proposes a model for SBE. This model is aligned with conscious capitalism, constructive capitalism, shared value, values-driven organizations and corporate governance. The paper includes a comparison between this model and the most popular excellence models. Research limitations/implications: This paper paves the way for more empirical and theoretical research on stakeholders' business excellence models. Practical implications: This model can be adopted by different national and international excellence awards. The adoption of this model can improve the benefits of shareholders, partners, customers, employees and the society at large. Implementing this model may be effective in transferring knowledge about conscious capitalism, values-driven organization and corporate governance to corporations worldwide. Social implications: This may contribute to protecting the environment and reducing economic inequalities that have caused political and social instability. Originality/value: Excellence models have been widely used with significant success all over the world. Although these models paid attention to customers and employees, they still reflect traditional capitalism that focuses on shareholders' value. This model is aligned to new economic trends that foster sustainability and improve benefits of all stakeholders.